A Thermosalient and Mechanically Compliant Organic Crystalline Optical Waveguide Switcher - Di, Qi (2024)
The dense and ordered molecular arrangements endow dynamic molecular crystals with fast response, rapid energy conversion, low energy dissipation, and strong coupling between heat/light and mechanical energy. Most of the known dynamic crystals can only respond to a single stimulus, and materials that can respond to multiple stimuli are rare. Here, we report an organic crystalline material that can be bent plastically and is also thermosalient, as its crystals can move when they undergo a reversible phase transition. The crystals transmit light regardless of their shape or crystalline phase. The combination of light transduction and reversible thermomechanical deformation provides an opportunity to switch the waveguiding capability of the material in a narrow temperature range, which holds a tremendous potential for applications in heat‐averse electronic components, such as central processing units. Unlike existing electronics, the material we report here is completely organic and therefore much lighter, potentially reducing the overall weight of electronic circuits.